Health Behaviors and Lifestyle Interventions in African American Breast Cancer Survivors: A Review - Paxton, Raheem J.; Garner, William; Dean, Lorraine T.; Logan, Georgiana; Allen-Watts, Kristen (Frontiers in Oncology, 2019)
Background: African American breast cancer survivors have a higher incidence of estrogen receptor negative and basal-like (e.g., triple negative) tumors, placing them at greater risk for poorer survival when compared to women of other racial and ethnic groups. While access to equitable care, late disease stage at diagnosis, tumor biology, and sociodemographic characteristics contribute to the disparities that exist between African American and Non-Hispanic White breast cancer survivors, poor lifestyle characteristics (i.e., inactivity, obesity, poor diet) contribute equally to these disparities. Lifestyle interventions hold promise in shielding African American survivors from second cancers, comorbidities, and premature mortality, but they are underrepresented in epidemiological and lifestyle intervention studies. This review examined the available literature to document health behaviors and lifestyle intervention (i.e., obesity, physical activity, and sedentary behavior) studies in African American breast cancer survivors. Methods: We used PubMed, Academic Search Premier, and Scopus to identify cross-sectional and intervention studies examining the lifestyle behaviors of African American breast cancer survivors. Identified intervention studies were critiqued for risk of bias. Other articles were identified and described to provide context for the review. Results: Our systematic review identified 226 relevant articles. The cross-sectional articles indicated poor adherence to physical activity and dietary intake and high rates of overweight and obesity. The 16 identified intervention studies indicated reasonable to modest study adherence rates (>70%), significant reductions in weight (range -1.9% to -3.6%), sedentary behavior (-18%), and dietary fat intake (range -13% to -33%) and improvements in fruit and vegetable intake (range +25% to +55%) and physical activity (range +13% to +544%). The risk of bias for most studies was high (44%) or moderate (44%). Conclusions: The available literature suggests that African American breast cancer survivors adhere to interventions of various modalities and are capable of making modest to significant changes. Future studies should consider examining (a) mediators and moderators of lifestyle behaviors and interventions, (b) biological outcomes, and (c) determinants of enhanced survival in this population.